Pengembangan SIAKAD Pada Politeknik Anika Palembang Berbasis Web Menggunakan Metode Web Engineering - Triana Wulandari; Hadi Syaputra; Afriyudi; Megawaty (JUPITER (Jurnal Penelitian Ilmu dan Teknologi Komputer), 2022)
Anika Polytechnic is one of the private universities in South Sumatra Province, precisely in the city of Palembang. To improve the quality of services to students at anika Polytechnic, one of the efforts that has been made is to build an academic information system. Anika Polytechnic has 20 permanent lecturers and 105 active students. So far, the process of daily activities mechanism at Anika Polytechnic has been carried out using a system even though the system is still desktop-based. So that the process of entering the lecture schedule is still carried out by the campus admin and cannot be done online. The solution to this problem is to build a web-based academic information system using PHP and MySQL programming languages as a database to store data developed using web engineering methods. Keywords—academic information systems, web-based, web engineering